Analisis Response Time Penatalaksanaan Rujukan Kegawatdaruratan Obstetri Ibu Hamil - Dwi Ayu Tirtaningrum; Ayun Sriatmi; Antono Suryoputro (Media Kesehatan Masyarakat Indonesia, 2018)
Semarang government established PONED Health Center and PONEK Hospital for referral in managingobstetric cases. In fact, response time referral is still long to get the service by patients. Research purposes,analyze of response time in the management obstetric maternal emergency referral in Semarang. Type of surveyresearch with qualitative descriptive approach and purposive technique. Data collection using indepth interviews,documentation, and source triangulation.The results, response time implementation and acceptance of referral hasnot been optimal as patient expectation. Length of time the patient came to the emergency room of Health Centeruntil ready referred to the PONEK Hospital 1-2 hours. Length of time the patient receives at the emergency roomof PONEK Hospital until get treatment room 2 -3 hours. The problem because responsiveness of the medical teamresponding to patients, maternal not carrying MCH books and not completing administrative, ambulance driverdifficult to contact, confirmation of information from referral hospital and duration of patients transfer processfrom delivery room to treatment room.